Crimea, Donbass and the Russo-Ukrainian War: The effect of the Minsk Agreements on the Finlandization of Ukraine - Tudela, Felipe (2021)
This article will analyze the Russo-Ukrainian war, which encompasses geographic, political, and pre and post-Soviet ethno-cultural factors between the two nations which share an ancient and rich history, characterized by the eternal conflict for control of the territory known today as Ukraine. These factors have divided the country and its population between the West and the East. This dispute inextricably encompasses questions of national identity and the emergence of new post-Soviet national identities. Making Ukraine a victim of its geography, due to the importance of this territory for the West and the East. Geostrategic importance evidenced by NATO’s advance to the East and Russia’s response to this advance. Likewise, the contemporary conflict with its origins in the Orange Revolution of 2004 will be addressed. In addition, we will address the long-term consequences of the Minsk Agreements and the role they will play in the possible Finlandization of Ukraine and the annexation of the Donbas region by Russia. Similarly, evaluate the conflict from realpolitik, and highlight the importance of political realism in the international arena.